High Frequency Breast Imaging: Experimental Analysis of Tissue Phantoms - Duy Hai Nguyen (IEEE, 2021)
This article presents the experimental proof of concept of high–frequency microwave breast imaging system operating from 16 to 20 GHz. At those frequencies the wavelengths are in the order of millimeter range which support better resolution in localizing cancerous tumors compared to the conventional microwave imaging systems. A new antenna is developed with a compact size of 7 $× $ 7 mm 2, which relies on an ultra-wideband, planar bowtie-like antenna structure. Practical results show that a bandwidth of 23.45 GHz is achieved (16 – 40 GHz) for a reflection loss higher than 10 dB. Furthermore, artificial breast tissue models based on glycerol–oil mixture with agar powder are developed. Dielectric properties of the tissue are stable over a wide frequency range up to 20 GHz at room temperature. The typical high microwave power losses within biological tissue at the operating frequency range are addressed by contacting the antennas directly to the tissue and slightly compressing the phantom without any coupling medium. Hence, the compressed breast geometry has a flat surface with well–defined boundaries, which simplifies tumor localization algorithms. For the purpose of demonstrating the current stage of research, a one–dimensional scanning system is used to localize the tumor’s positions inside the simulated, heterogeneous breast model of 36 mm thickness. Using the root mean square deviation algorithm, we can accurately detect positions of the tumors, which have a cross-sectional area down to 4 $× $ 4 mm 2. The preliminary results show the feasibility of achieving a high resolution with a compact microwave system for early-stage breast cancer detection.